Problemy metodologiczne w badaniach nad Celtami i celtyckością - Faszcza, Michał Norbert (Studia Europaea Gnesnensia, 2015)
In the studies devoted to Celts so far, researchers have tried to define “Celticness” based on two criteria: their material culture and language. Another element which tended to be employed was the argument of terminology used by antique authors. At present, we know that the sense of ethnic identification may have been independent of those factors. This led to a genuine “scientific revolution”, which resulted in the exclusion of Ireland and northern Britain from the circle of Celtic culture. Consequently, the question in which cases one can speak of “Celticness” has become relevant yet again. The author is of the opinion that decisive significance should be attributed to self-identification of given tribes, although sources rarely provide information in that respect. Depending on the remaining criteria tends to be greatly unreliable, given that they were are a modern concept and as such are subject to manipulation. A comfortable, though exceedingly rare situation is their joint occurrence. For this reason the author is inclined to give priority to the language criterion, yet only when the faulty terminology relation to the so-called Q-Celtic and P-Celtic languages is abandoned. Despite the fact that Irish civilisation has been demonstrated to have been non-Celtic, the obsolete terminology is still in use, as a result of which the linguistic criterion cannot perform its function effectively.